(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To identify factors associated with pathological complete response after long-course preoperative chemoradiotherapy in patients with middle and lower rectal cancer. Subjects and Methods: A retrospective descriptive and analytical study was conducted on 168 patients with stage II–III middle and lower rectal cancer who underwent long-course preoperative chemoradiotherapy followed by radical surgery. Pathological complete response was defined as the absence of viable tumor cells in the primary tumor bed in the surgical specimen, corresponding to Mandard TRG 1/ypT0. Clinical, laboratory, and imaging-related factors were analyzed using univariate tests and multivariable logistic regression. Results: The pathological complete response rate was 22.0% (37/168). Patients with pathological complete response had a significantly smaller pretreatment tumor size than those without pathological complete response (4.78 ± 1.90 cm vs. 5.81 ± 2.25 cm; p = 0.006) and lower pretreatment CEA levels [2.37 (1.15–3.28) vs. 4.57 (2.55–7.94) ng/mL; p < 0.001]. In multivariable analysis, pretreatment CEA >5 ng/mL was an independent unfavorable factor for pathological complete response (OR = 0.33; 95%CI: 0.14–0.81; p = 0.015). After chemoradiotherapy, mrTRG 1–2 was strongly associated with pathological complete response. Conclusion: Low pretreatment CEA, smaller baseline tumor size, and post-treatment mrTRG 1–2 were suggestive factors associated with a higher probability of pathological complete response after long-course preoperative chemoradiotherapy.